PSYCHOSOCIAL AND DEMOGRAPHIC PREDICTORS OF COUNSELLING HELP-SEEKING AMONG ADOLESCENTS IN IJEBU-ODE, OGUN STATE - King-Oladipo, Christianah Patience; Owoyele, Jimoh Wale; Oladipo, Samuel Ekundayo; Oarhe-Adekola, Obofoni Ekiomoado (African Journal of Social and Behavioural Sciences, 2025)
Globally, adolescence is considered a critical developmental stage, with recent concerns highlighting a decline in adolescents’ mental well-being, largely due to social media’s influence, leading to increased mental health issues and psychosocial problems requiring professional intervention. Despite these, many adolescents do not seek help, and those who do often face barriers. This study investigated the psychosocio-demographic predictors of counselling helpseeking behaviour among Senior Secondary School students in Ijebu-Ode. Using a correlational survey design, 247 randomly sampled students completed validated measures assessing helpseeking behavior, belief in counseling, counselor’s disposition, fear of stigma, and self-disclosure risk. Three null hypotheses were tested at .05 level of significance, and results revealed significant negative correlations between birth order, being a day or boarder student, belief in counselling effectiveness, and help-seeking behaviour (r = -.23, -.15, -.22) respectively. Conversely, birth order correlated positively with self-disclosure risk (r = .14). No significant relationships were found with age, fear of stigma, counselor’s disposition, or school type. Psychosocio-demographic variables jointly accounted for 63.8% of the variance in help-seeking behavior (R² = .638, p < .001). Psychological factors also independently influenced help-seeking, whereas socio-demographic variables did not. The study concluded that psychological variables significantly predicted students’ help-seeking behaviour, and to enhance help-seeking, schools should promote awareness, improve counselling services, and collaborate with stakeholders to reduce stigma.